The Differences of Compound Words from Word Combinations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the differences between compound words and word combinations in the Karakalpak language. Compound words and word combinations are compared with each other and their characteristic features are determined.